2022
DOI: 10.1038/s41467-022-31440-y
|View full text |Cite
|
Sign up to set email alerts
|

Existing function in primary visual cortex is not perturbed by new skill acquisition of a non-matched sensory task

Abstract: Acquisition of new skills has the potential to disturb existing network function. To directly assess whether previously acquired cortical function is altered during learning, mice were trained in an abstract task in which selected activity patterns were rewarded using an optical brain-computer interface device coupled to primary visual cortex (V1) neurons. Excitatory neurons were longitudinally recorded using 2-photon calcium imaging. Despite significant changes in local neural activity during task performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…1f). Reversion has been observed in various different contexts, such as reaching tasks (Perich and Miller, 2017, Cherian et al, 2013), BCI tasks in visual cortex (Jeon et al, 2022), and in the remapping of hippocampal place fields (Alme et al, 2014). This would indicate that the neural activity we observed in M1 during performance of a task can be unaffected by an intervening learning experience.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1f). Reversion has been observed in various different contexts, such as reaching tasks (Perich and Miller, 2017, Cherian et al, 2013), BCI tasks in visual cortex (Jeon et al, 2022), and in the remapping of hippocampal place fields (Alme et al, 2014). This would indicate that the neural activity we observed in M1 during performance of a task can be unaffected by an intervening learning experience.…”
Section: Resultsmentioning
confidence: 99%
“…It could have been that motor memories were stored in a manner that is not detectable when another action is being performed (Herzfeld et al, 2014, Jeon et al, 2022), nor be present in the same neural activity when it is driving behavior. For example, in our experiments, the motor memory could have been stored (perhaps outside of M1) such that the memory is only detectable in M1 the appropriate behavior is being performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with RL, human intelligence has a superior cognition ability and higher flexibility. The human brain processes the sensory information from the external environment through the sensory system to obtain abstract semantic information [41][42][43] . Then, the cognition control system, namely, the prefrontal cortex (PFC), integrates semantic information and knowledge from the memory to make decisions [37][38][39][40] .…”
Section: A Framework Of Cognitive Escape Reinforcement Learningmentioning
confidence: 99%
“…Investigations have found that human beings have a high-level cognitive control module in the brain to get rid of the local optimum [37][38][39][40] and make a better decision and that human beings can deal with various information from different scenarios since their brains abstract primary sensory information into high-level semantics for decision-making [41][42][43] , rather than dealing with numerous low-level information directly. The superior cognition ability and higher flexibility displayed by humans can enlighten to open up new avenue for addressing the above-mentioned challenging problems of RL.…”
mentioning
confidence: 99%